New diagnostic framework makes integrated water storage a reality - Lautze, Jonathan F. (CGIAR, 2023)
In 2010, water levels at Lake Kariba were so high that the Kariba Dam had to be opened to prevent flooding. By January 2023, capacity at the world’s largest artificial lake, which straddles the Zimbabwe–Zambia border, had plunged to just 2 percent. Water levels have risen slightly since then, but the lake’s wild fluctuations in volume have sparked serious concern for water and energy security in both countries.